2019
DOI: 10.1002/ajhb.23341
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and movement behaviors among schoolchildren from 13 countries across a continuum of human development indices: A multinational cross‐sectional study

Abstract: Objective This study describes the distributions of body mass index (BMI) and movement behaviors among schoolchildren from 13 countries across a continuum of human development. Methods Data were from a cross‐sectional study of 9‐11‐year‐old children (n = 8055) recruited from 269 urban schools in 13 countries, and an additional 7 rural schools in one of these countries (Mozambique). BMI was derived from objectively measured heights and weights. Moderate‐ to vigorous‐intensity physical activity (MVPA), sedentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…These differences in gender and meeting physical activity recommendations have also been reported in other studies using objective measures [48]. The trend of a higher proportion of boys meeting sleep guidelines but a lower proportion of them meeting SVT guidelines compared to girls in this study was also previously reported in studies from China [31], Canada [49], Europe [50], and Korea [33]. Interventions aimed at improving lifestyle behaviours amongst youth in Asian countries might consider having more resources and support targeting girls because they have been shown consistently in this study to be less active and receive less sleep.…”
Section: Discussionsupporting
confidence: 88%
“…These differences in gender and meeting physical activity recommendations have also been reported in other studies using objective measures [48]. The trend of a higher proportion of boys meeting sleep guidelines but a lower proportion of them meeting SVT guidelines compared to girls in this study was also previously reported in studies from China [31], Canada [49], Europe [50], and Korea [33]. Interventions aimed at improving lifestyle behaviours amongst youth in Asian countries might consider having more resources and support targeting girls because they have been shown consistently in this study to be less active and receive less sleep.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, although adjustment was undertaken for the many factors implicated in fracture incidence in the literature, the prevalence of participation in sporting activities and general patterns of activity in addition to some medical factors (such as steroid use, chronic kidney disease) within this cohort is unknown. There is some evidence of BMIz being negatively associated with physical activity levels in older children, but elaboration of physical activity levels is not possible within this study of preschool children …”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of BMIz being negatively associated with physical activity levels in older children, but elaboration of physical activity levels is not possible within this study of preschool children. (83) Future research This work suggests that interventions to treat obesity in early childhood could have benefits for the primary or secondary prevention of fractures later in childhood, especially in the prevention of fractures within the forearm and hand or foot and ankle. Although initial studies investigating the impact of weight loss upon bone health in children and adolescents have found improved physical activity levels and improved bone mass, further work is needed to determine the overall impact of pediatric weight loss upon bone health, especially considering the evidence for bone density loss associated with weight reduction in adults.…”
Section: Strengths and Weaknesses Of This Studymentioning
confidence: 99%
“…However, recall methods, such as questionnaires, are challenging and less reliable for children than adults (Chinapaw et al, 2010 ; Sirard & Pate, 2001 ) as young children have often not developed the capacity for introspection; self-report, therefore has its limitations. Therefore, objective methods like accelerometry are widely used internationally to assess PA in children and adolescents (Brazendale et al, 2021 ; Cooper et al, 2015 ; Manyanga et al, 2020 ; Troiano et al, 2014 ). Accelerometers are worn across the waist and are simply operated; moreover, they objectively evaluate PA, and their validity has been confirmed (Evenson et al, 2008 ; Kumahara et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%